A Hydrodynamic Study of a Fast‐Bed Dual Circulating Fluidized Bed for Chemical Looping Combustion. Issue 10 (6th July 2016) - Haider, Syed K.; Duan, Lunbo; Patchigolla, Kumar; Anthony, Edward J.
Abstract: This study explores the use of a dual interconnected circulating fluidized bed (CFB) for chemical looping combustion. This design can enhance gas–solid interactions, but it is difficult to control the solid transfer and circulation rates. With the use of a 1:1 scale cold‐flow model, an investigation determining the hydrodynamic behavior of the dual CFB system has been conducted. The cold‐flow system consists of two identical fast‐bed risers, each with an internal diameter of 100 mm and a height of 7 m. The simplified cold‐flow model is based on the chemical looping Pilot‐Scale Advanced CO2 Capture Technology (PACT) facility at Cranfield. Here, we have determined the minimum fluidization and transport velocities, and we have assessed the solid density profiles, transport capacity, and potential for the dilution by air/N2 leakage into the CO2 stream exiting the fuel reactor. The experimental procedure uses two different bed materials, molochite (ceramic clay) and FE100 (iron particles), and it satisfies the dynamic scaling laws to model the bed inventory within the system. The results indicate that the two fast‐bed risers share similar density and pressure profiles. Stable circulation can be achieved through pneumatic transport. The circulation rate of the system is flexible and can be adjusted by altering the fluidization velocity in the riser and by altering the bed inventory. The gas leakage from the loop seal to the cyclone was found to be sensitive to the bed height and fluidization velocity in the loop seal. However, by maintaining a loop‐seal bed height above 600 mm during operation, the outlet stream remains undiluted. Abstract : Hydrodynamic Results : A 1:1 scale cold flow model is used to study the hydrodynamic behavior and characteristics of a dual interconnected circulating fluidized bed (CFB) pilot plant chemical looping reactor (right). This investigation determines that both risers have similar density profiles allowing for stable operation to be maintained through pneumatic transport. Gas leakage varies with the loop‐seal bed height and can be controlled and minimized by maintaining the loop‐seal bed height above 600 mm.